2009
DOI: 10.1074/jbc.m109.004796
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and Tensin Homologue on Chromosome 10 (PTEN) Directs Prostaglandin E2-mediated Fibroblast Responses via Regulation of E Prostanoid 2 Receptor Expression

Abstract: Prostaglandin E 2 (PGE 2 ) is an arachidonic acid metabolite that counters transforming growth factor-␤-induced fibroblast activation via E prostanoid 2 (EP2) receptor binding. Phosphatase and tensin homologue on chromosome 10 (PTEN) is a lipid phosphatase that, by antagonizing the phosphoinositol 3-kinase (PI3K) pathway, also inhibits fibroblast activation. Here, we show that PTEN directly regulates PGE 2 inhibition of fibroblast activation by augmenting EP2 receptor expression. The increase in collagen produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
16
1
Order By: Relevance
“…Nevertheless, we consider it pertinent that COX-2, mPGES-1, and EP2 are each subject to a feed-forward process by PGE 2 in other cell lineages. Thus, PGE 2 synthesized from inducible COX-2 and mPGES-1 initiates signals that further increase mRNA/protein levels of COX-2, mPGES-1, and EP2 (48)(49)(50)(51)(52). In support of such a feed-forward process in B cells is preliminary evidence that pulsing cultures with PGE 2 does augment COX-2 and EP2 mRNA and/or protein.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, we consider it pertinent that COX-2, mPGES-1, and EP2 are each subject to a feed-forward process by PGE 2 in other cell lineages. Thus, PGE 2 synthesized from inducible COX-2 and mPGES-1 initiates signals that further increase mRNA/protein levels of COX-2, mPGES-1, and EP2 (48)(49)(50)(51)(52). In support of such a feed-forward process in B cells is preliminary evidence that pulsing cultures with PGE 2 does augment COX-2 and EP2 mRNA and/or protein.…”
Section: Discussionmentioning
confidence: 95%
“…Third, EP2 and EP4, two PKA-activating receptors for PGE 2 (45), are expressed on activated B cells and reported to function in augmenting IgG and IgE synthesis (46,47). Finally, studies in nonlymphoid cells show that the COX-2 pathway is subject to significant positive feedback control; COX-2-driven PGE 2 can promote the further upregulation of COX-2 (48-50), downstream PGE 2 synthase (51), and EP2 (52). Thus, the progressive increase in AID within cycling B cells might reflect the influences of an increasingly functional COX-2/PGE 2 pathway during B cell clonal expansion.…”
mentioning
confidence: 99%
“…Our group previously established that PGE 2 prevents expression of contractile genes such as ␣-SMA in lung fibroblasts (18,19). Recently, we have also demonstrated that PGE 2 can reverse already established myofibroblast differentiation induced in lung fibroblasts by TGF-␤1 as well as endothelin-1 (20).…”
Section: Differentiation Of Lung Fibroblasts Into Contractile Proteinmentioning
confidence: 89%
“…EP 2 receptors are G s -coupled and mediate increases in cAMP (Regan et al, 1994b). A positive feedback loop whereby cAMP signaling enhances EP 2 receptor expression has been suggested (Sagana et al, 2009). Changes in cAMP levels produce pleiotropic effects by activating cAMP-binding proteins.…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%